2005
DOI: 10.2337/diacare.28.11.2703
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Gastric Banding Prevents Type 2 Diabetes and Arterial Hypertension and Induces Their Remission in Morbid Obesity

Abstract: OBJECTIVE -Lifestyle modifications and pharmacological interventions can prevent type 2 diabetes in obese subjects with impaired glucose tolerance. The aim of this study was to compare laparoscopic adjustable gastric banding (LAGB) and conventional diet (No-LAGB) in the prevention (primary intervention study; 56 vs. 29 patients) and remission (secondary intervention study; 17 vs. 20 patients) of type 2 diabetes and hypertension in grade 3 obesity in a 4-year study.RESEARCH DESIGN AND METHODS -The subjects (n ϭ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(75 citation statements)
references
References 43 publications
2
72
0
1
Order By: Relevance
“…Studies of the pharmacological treatment of obesity have been characterised by high drop-out rates, low sustainability, and side effects; weight loss medications cannot be recommended as a primary therapy for diabetes at this time. In addition to the beneficial effects of weight loss on glycaemia, weight loss and exercise improve coincident CVD risk factors, such as blood pressure and atherogenic lipid profiles, and ameliorate other consequences of obesity [37][38][39][40]. There are few adverse consequences of such lifestyle interventions other than the difficulty in incorporating them into usual lifestyle and sustaining them, and the usually minor musculoskeletal injuries and potential problems associated with neuropathy, such as foot trauma and ulcers, that may occur with increased activity.…”
Section: Principles In Selecting Antihyperglycaemic Interventionsmentioning
confidence: 99%
“…Studies of the pharmacological treatment of obesity have been characterised by high drop-out rates, low sustainability, and side effects; weight loss medications cannot be recommended as a primary therapy for diabetes at this time. In addition to the beneficial effects of weight loss on glycaemia, weight loss and exercise improve coincident CVD risk factors, such as blood pressure and atherogenic lipid profiles, and ameliorate other consequences of obesity [37][38][39][40]. There are few adverse consequences of such lifestyle interventions other than the difficulty in incorporating them into usual lifestyle and sustaining them, and the usually minor musculoskeletal injuries and potential problems associated with neuropathy, such as foot trauma and ulcers, that may occur with increased activity.…”
Section: Principles In Selecting Antihyperglycaemic Interventionsmentioning
confidence: 99%
“…The most convincing long-term data indicating that weight loss effectively lowers glycaemia have been generated in the follow-up of type 2 diabetic patients who have had bariatric surgery. In this setting, with a mean sustained weight loss of >20 kg, diabetes is virtually eliminated [42][43][44][45]. In addition to the beneficial effects of weight loss on glycaemia, weight loss and exercise improve coincident CVD risk factors, such as blood pressure and atherogenic lipid profiles, and ameliorate other consequences of obesity [41,46,47].…”
Section: Lifestyle Interventionsmentioning
confidence: 99%
“…Whichever method is used, numerous short-and medium-term studies have confirmed that bariatric surgery is superior to conventional, non-operative methods in inducing weight loss and resolving comorbidities. [9][10][11] Although long-term data are more limited, it generally supports the durability of operative methods. In a recent 4-year randomized comparison of laparoscopic Roux-en-Y-gastric bypass (LRYGB) and laparoscopicadjusted gastric band, excess weight loss was noted to be 68.4% and 45.4% respectively.…”
Section: Introductionmentioning
confidence: 99%